International nuclear energy legal regulation: comparing the experience of the EU and the CIS countries - Nukusheva, Aigul; Karzhassova, Guldana; Rustembekova, Dinara; Au, Tatyana; Baikenzhina, Kulbagila (International environmental agreements : politics, law and economics, 2021)
The world community recognizes the enormous potential danger posed by nuclear power, including accidents at nuclear industries and atomic infrastructure facilities, the possibility of using nuclear technologies for criminal purposes. At the same time, immediate rejection of the use of nuclear technologies can create incomparably greater harm to both humans and the environment. In the context of many countries' transition to a low-carbon economy, nuclear energy is assigned a special role. The subject of this study is political and legal prerequisites for expanding legal regulation in the field of nuclear energy. Using the method of political and legal analysis, the study considers modern international initiatives in legal regulation of nuclear energy. In addition, the work touches on the issue of the relationship between nuclear law and private international law in the context of the possibility of expanding the latter. The study suggests that in the near future, the expansion of nuclear energy legal regulation at the EU and CIS level will be carried out mainly with the help of soft law acts, as well as bilateral treaties concerning the technical aspects of nuclear infrastructure facilities. In practical terms, this study is of interest to lawyers in the field of public international, private international, and energy law.